MiR-215-5p is a tumor suppressor in colorectal cancer targeting EGFR ligand epiregulin and its transcriptional inducer HOXB9. (November 2017) - Vychytilova-Faltejskova, Petra; Merhautova, Jana; Machackova, Tana; Gutierrez-Garcia, Irene; Garcia-Solano, José; Radova, Lenka; Brchnelova, Dominika; Slaba, Katerina; Svoboda, Marek; Halamkova, Jana; Demlova, Regina; Kiss, Igor; et al.
Abstract Growing evidence suggests that microRNAs are involved in the development and progression of colorectal cancer (CRC). In the present study, deregulation and functioning of tumor-suppressive miR-215-5p was evaluated in CRC. In total, 448 tumor tissues and 325 paired adjacent healthy tissues collected from Czech and Spain cohorts of CRC patients have been used for miR-215-5p expression analyses. A series of in vitro experiments have been performed using transient transfection of miR-215-5p mimics into four CRC cell lines to identify specific cellular processes affected by miR-215-5p. Further, the effects of miR-215-5p on tumor growth were evaluated in vivo using NSG mice and stable cell line overexpressing miR-215-5p. Target mRNAs of miR-215-5p were tested using luciferase assay and western blot analyses. We found that miR-215-5p is significantly downregulated in tumor tissues compared with non-tumor adjacent tissues and its decreased levels correlate with the presence of lymph node metastases, tumor stage, and shorter overall survival in CRC patients. Overexpression of miR-215-5p significantly reduced proliferation, clonogenicity, and migration of CRC cells, lead to cell cycle arrest in G2/M phase and p53-dependent induction of apoptosis. The ability of miR-215-5p to inhibit tumor growth was confirmed in vivo. Finally, we confirmed epiregulin and HOXB9 to be the direct targets of miR-215-5p. As epiregulin is EGFR ligand and HOXB9 is its transcriptional inducer, we suggest that the main molecular link between miR-215-5p and CRC cells phenotypes presents the EGFR signaling pathway, which is one of the canonical pathogenic pathways in CRC.